An outline of Christopher Dawson's philosophy of culture - Zenderowska, Magdalena (Folia Philosophica, 2000)
In the past we had to do with many different cultures and religions. Christopher Dawson tries to unite them to form, in this way, a coherent view of reality. Being one on the most outstanding representatives of cultural studies at the beginning of the 20th c. he shared the conviction the civilisation of the West was undergoing a deep crisis. Dawson, having analysed a vast research material, provides his own explanation of the state of the contemporary culture, defining it as a crisis of the idea of progress. He strives to find a way out of this quandary, and, following strictly the idea of the tight connection between culture and religion, he comes across the idea of rechristianisation”. He unmasks, at the same time, the illusions Europe fell prey to during the last two centuries. His criticism of the idea of progress thought of as a kind of religion is not, however, only an attempt to reject what he perceived as evil. This criticism was based on that idea’s having failed to fulfil in practice the expectations associated with it. The deficiency of certain elements necessary in culture brought about a state of crisis, and now hawe to find the causes of that crisis and the ways to overcome it. Of foremost importance in this process are the moral carried by religions. Starting then with the origin of culture, Dawson characterises its development, transformations, and the threats it faces, and finally arrives at some constructive conclusions.